ANALISIS REVIEW ONLINE TERHADAP REPUTASI HOTEL NOVOTEL GOLF RESORT AND CONVENTION CENTER MANADO - Bet El Silisna Lagarense; Mita Takaendengan; Aldi B.K.T Kaunang (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2024)
One of the advancements in technology is the internet. Internet services can be accessed freely from anywhere and anytime with a website. By utilizing a website or application, one of the benefits is helping us find information quickly. Online reviews, as part of internet usage, are systems often integrated into applications and websites. These reviews are very helpful for prospective customers to assess product quality accurately. By examining guest reviews, potential customers can evaluate how good the products or services of a company are. Qualitative research, which is descriptive and emphasizes analysis, process, and meaning from the subject's perspective, is highlighted in this study. It uses a theoretical basis as a guide to ensure the research focus aligns with real-world facts. Unlike quantitative methods, qualitative research produces findings that cannot be obtained through statistical procedures or measurement methods. Based on the author's analysis, online reviews significantly impact a hotel's reputation. This study aims to answer the research question on